The Radical How - Greenway, Andrew; Loosemore, Tom (Nesta and Public Digital, 2024)
Any mission-focused government should be well equipped to define, from day one, what outcomes it wants to bring about. But radically changing what the government does is only part of the challenge. We also need to change how government does things. The usual methods, we argue in this paper, are too prone to failure and delay. There’s a different approach to public service organisation, one based on multidisciplinary teams, starting with citizen needs, and scaling iteratively by testing assumptions. We’ve been arguing in favour of it for years now, and the more it gets used, the more we see success and timely delivery. We think taking a new approach makes it possible to shift government from an organisation of programmes and projects, to one of missions and services. It offers even constrained administrations an opportunity to improve their chances of delivering outcomes, reducing risk, saving money, and rebuilding public trust. The Radical How in a nutshell The struggles and shortcomings of delivering in government are well rehearsed. Many of the root causes that make it tough have been restated several times over several decades. But what to do? We believe the government can and should change how it delivers, by: organising around multidisciplinary teams embracing incremental, feedback-driven iteration focusing more on outcomes. The Radical How is a change of mindset as much as a change in organisation. It promotes methods and processes that have been shown to work, multiple times, at scale. They are the default ways of working for many of the world’s most successful companies. However, the occasions where they have been deployed are rare in government. These occasions have come about thanks to exceptional leaders, exceptional circumstances, or both. We think they’d make a big difference if they became the norm, rather than the exception. We also think that without them, mission oriented government will not become a reality. New policy ideas will remain just that, rather than translating into profound improvements to society. Central to this approach is the widespread adoption of internet-era ways of working. This paper explains both those and our thinking in more detail, with reference to real examples.

The Big Con: How the Consulting Industry Weakens our Businesses, Infantilizes our Governments and Warps our Economies - Mazzucato, Mariana; Collington, Rosie (Allen Lane, 2023)
There is an entrenched relationship between the consulting industry and the way business and government are managed today which must change.Mariana Mazzucato and Rosie Collington show that our economies' reliance on companies such as McKinsey, Boston Consulting Group, Bain & Company, PwC, Deloitte, KPMG and EY stunts innovation, obfuscates corporate and political accountability and impedes our collective mission of halting climate breakdown.The 'Big Con' describes the confidence trick the consulting industry performs in contracts with hollowed-out and risk-averse governments and shareholder value-maximizing firms. It grew from the 1980s and 1990s in the wake of reforms by both the neoliberal right and Third Way progressives, and it thrives on the ills of modern capitalism, from financialization and privatization to the climate crisis. It is possible because of the unique power that big consultancies wield through extensive contracts and networks - as advisors, legitimators and outsourcers - and the illusion that they are objective sources of expertise and capacity. To make matters worse, our best and brightest graduates are often redirected away from public service into consulting. In all these ways, the Big Con weakens our businesses, infantilizes our governments and warps our economies.Mazzucato and Collington expertly debunk the myth that consultancies always add value to the economy. With a wealth of original research, they argue brilliantly for investment and collective intelligence within all organizations and communities, and for a new system in which public and private sectors work innovatively for the common good. We must recalibrate the role of consultants and rebuild economies and governments that are fit for purpose.

Scaling the impact of sustainability initiatives: a typology of amplification processes - Lam, David P. M.; Martín-López, Berta; Wiek, Arnim; Bennett, Elena M.; Frantzeskaki, Niki; Horcea-Milcu, Andra I.; Lang, Daniel J. (Urban Transformations, 2020)
Amplifying the impact of sustainability initiatives to foster transformations in urban and rural contexts, has received increasing attention in resilience, social innovation, and sustainability transitions research. We review the literature on amplification frameworks and propose an integrative typology of eight processes, which aim to increase the impact of such initiatives. The eight amplification processes are: stabilizing, speeding up, growing, replicating, transferring, spreading, scaling up, and scaling deep. We aggregated these processes into three categories: amplifying within, amplifying out, and amplifying beyond. This integrative typology aims to stimulate the debate on impact amplification from urban and rural sustainability initiatives across research areas to support sustainability transformations. We propose going beyond an understanding of amplification, which focuses only on the increase of numbers of sustainability initiatives, by considering how these initiatives create transformative change.
Keywords: City; Rural; Scaling; Transformation; Transition; Transition initiative; Urban

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Building a culture of learning at scale: learning networks for systems change. - McKenzie, Fiona (Orange Compass & Paul Ramsay Foundation, 2021)
This scoping paper explores the question ‘what would it take to build a culture of learning at scale?’. It focuses on systems-wide learning that can help to inform systems change efforts in complex contexts. To answer this question, literature was reviewed from across diverse disciplines and the realms of education, innovation systems, systems thinking and knowledge management. This inquiry was also supported by in-depth interviews with numerous specialists from the for-purpose sector and the examination of several case studies of learning across systems. The goal was to derive common patterns to inform a ‘learning for systems change’ framework. Learning for systems change is critical when working with complexity. The dynamic nature of complex adaptive systems requires an ability to continually sense and learn from the system and adapt accordingly. This is because the nature of the challenge and ‘what works’ to meet the challenge is continually shifting (Lowe and Plimmer, 2019). This requires an ongoing process of iterative inquiry that draws upon wisdom and insights from across the system. Such learning challenges traditional siloes of expertise and organisational boundaries (Clarke et al., 2019). Learning is not simply a nice to have. It is critical for greater impact and improved outcomes, particularly in mission-driven organisations and initiatives (Price et al., 2019). In this paper, a ‘learning networks’ approach is proposed, one that draws upon individual, group and systems-wide learning to build capacity and resilience for systems change in uncertain environments. This fills a gap in the literature where the focus is largely on learning within organisations. Instead, the focus here is on what is required to support learning to occur across scales and boundaries - from the individual to system-wide. A simple meta-framework for developing learning networks is proposed that includes high level guidance on the enabling conditions - the mindsets, relationships, processes and structures- that would enable learning networks to flourish.